«Fuori dalla politica» ma dentro lo Stato. Il «lungo viaggio» di Giuseppe Tucci attraverso il fascismo: Appunti per una biografia - Crisanti, Alice (Studi e materiali di storia delle religioni, 2018)
The factors of the relationship between politics and culture take a peculiar form between the 19th and 20th century. As it has been accurately investigated by Luisa Mangoni and Gabriele Turi, such aspect vividly surfaces in all its problematic nature while retracing Giuseppe Tucci's personal and intellectual journey, along with his relationship to the Fascist regime, over the course of what has been called the «Twenty years of intellectuals». This paper aims to examine one of the «miniature stories» that bear testimony to the decision by most Italian intellectuals not to oppose Fascism, but to contribute through their work to the making of the regime's cultural apparatus. Far from reducing Tucci's choice to align himself with the totalitarian regime to mere opportunism, I will focus on one of the most fraught issues of his life, as an example of how politics has impacted the scientific research in Italy in the early 20th century. (English)